The Digital Era of Education in Pakistan: Integrating Technology and Pedagogical Innovation (Al-Aasar, 2024)
The integration of technology into education in Pakistan marks a new era that is transforming traditional teaching methods into more modern and effective ones. This study explores the various aspects of digital education in Pakistan, highlighting the importance of technologies that improve the learning process and provide inclusive opportunities for students. It examines e-learning platforms, online classes, and digital teaching resources that enhance students' learning abilities. Furthermore, the research addresses the challenges of inclusion, equity, and accessibility within digital education, emphasizing how it helps bridge the gap for students from different socio-economic backgrounds in Pakistan.